2021
DOI: 10.3390/ijerph182111546
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Barriers to the Access to Healthcare and Rehabilitation Services: A Qualitative Study with Mothers or Female Caregivers of Children with a Disability in Indonesia

Abstract: Accessibility to healthcare and rehabilitation services for children with a disability (CWD) is essential to improving their health and wellbeing. However, access to the services, especially in many settings in developing countries with scarcity of resources, is still limited. As part of a qualitative study exploring impacts of caring for CWD on mothers or female caregivers and their coping strategies, this paper describes barriers for access to healthcare and rehabilitation services for CWD in Belu district, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…These factors have been identified as heavily influencing patients’ preferences to seek medical treatment overseas. This scoping review supports previous findings which have reported that Indonesia has a comparably low ratio of qualified doctors to patients, and most prefer to work in private hospitals in urban areas within Indonesia [ 65 – 67 ], resulting in understaffing and the maldistribution of skilled staff within periphery areas [ 68 , 69 ]. It is suggested that with a population of about 270 million, Indonesia needs 270,000 doctors [ 70 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These factors have been identified as heavily influencing patients’ preferences to seek medical treatment overseas. This scoping review supports previous findings which have reported that Indonesia has a comparably low ratio of qualified doctors to patients, and most prefer to work in private hospitals in urban areas within Indonesia [ 65 – 67 ], resulting in understaffing and the maldistribution of skilled staff within periphery areas [ 68 , 69 ]. It is suggested that with a population of about 270 million, Indonesia needs 270,000 doctors [ 70 ].…”
Section: Discussionsupporting
confidence: 87%
“…Further, evidence suggests patients felt undervalued in Indonesian health systems and that their care was not prioritised. This was identified as stemming from factors including sparseness of health facilities, a shortage of qualified doctors, and trained staffs [ 69 , 71 ]. There is also evidence that patients sought more timely health care and treatment overseas as a consequence of long waiting time periods for medical treatment within Indonesia [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a future risk of public rejection of ASHUE vaccines. Our findings here are congruent with the concept of healthcare acceptability in the Access to Healthcare Framework, which suggests that the acceptance of a healthcare service is determined by how well it aligns with sociocultural norms and values, and religious beliefs of communities where the service is being delivered [ 31 33 ]. This study also highlights faith-related fatalism among social media users who underlined the importance of fearing God’s punishment instead of compliance with preventive measures or biomedical perception of risks.…”
Section: Discussionsupporting
confidence: 82%
“…Theme 6: Cost limitations Mothers who have children with disabilities experience limited costs of treatment (therapy) and education, especially if their husbands have irregular incomes. This is supported by research by Asa et al (2021) that the cause of financial constraints in families is due to lack of permanent work and increased health care costs. Theme 7: Obstacles in everyday life Children with disabilities who are unable to be independent have an impact on negative pressures on mothers and cause parenting stress (Rusmariana et al, 2021).…”
Section: Discussion Theme 1: Destinymentioning
confidence: 94%